Long Non-coding RNA Gas5 Is Associated With Preeclampsia and Regulates Biological Behaviors of Trophoblast via MicroRNA-21 - Zheng, Dongying; Hou, Yue; Li, Yuanyuan; Bian, Yue; Khan, Muhanmmad; Li, Fan; Huang, Ling; Qiao, Chong (Frontiers in Genetics, 2020)
Preeclampsia is a lethal pregnancy specific hypertensive disorder involving multisystem. Despite extensive studies to investigate the causes of preeclampsia, the pathogenesis still remains largely unknown. Long non-coding RNAs (lncRNAs) are a diverse class of non-translated RNAs which play an important role in various biological phenomena. Although lncRNA Growth Arrest-Specific 5 (GAS5) aberrantly expressed in multiple cancer tissues and is implicated in multiple biological processes of tumor cells, little is known about its role in preeclampsia. In this study, 40 patients with preeclampsia and 32 gestational age-matched normotension pregnant women were recruited. Using quantitative real-time polymerase chain reaction (qRT-PCR), we found higher expression of GAS5 in placenta of preclamsia affected women. The level of GAS5 existed strongly in correlation with Thrombin Time indicating coagulation function and other clinical parameters by Pearson correlation analysis. Then we constructed the GAS5 lentivirus expression vectors and transfected into human trophoblast cell lines JEG-3 and HTR-8/SVneo. Using in vitro cell culture studies, we found an inhibitory effect of GAS5 on proliferation, migration and invasion however; no effect on apoptosis was detected. Further mechanistic analysis found that GAS5 modulated microRNA-21(miR-21) in an opposite variation tendency by qRT-PCR and rescue experiment. In addition, inhibition of GAS5 promoted the activation of PI3K/AKT signaling pathway and its downstream proteins including MMP-9 and TP53 as evident from our qRT-PCR and western blot analyses. Thus, we suggested that GAS5 might have implication for the pathogenesis of preeclampsia by influencing the biological behavior of trophoblast cells through the regulation of miR-21 and activation of PI3K/AKT pathway and its downstream targets, which may contribute to reveal the nature of preeclampsia.